STRATEGI MEDIA RELATIONS HUMAS DALAM MEMBANGUN GOOD GOVERNANCE UNIVERSITAS RIAU - ", Marlia; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Building a media relations strategy, PR University of Riau using good cooperation with the media. Issues which occurred involving several elements of the Riau University involved in corruption, fraud and immoral make PR University of Riau should be able to give a good image to the public, especially the mass media. To the need to build a good relationship between the organization and the mass media so that the objectives of the organization / institution to achieve high publicity and publicity can be achieved with good and proper. Strategy needed teknk-technique or knowledge in the sense of understanding of media relations strategy, in order to be able to give you the satisfaction of cooperation between the two sides so that cooperation can be kept running continuously. This study aims to analyze the strategy of media relations PR Riau University in establishing good governance. Any form of managing relations, development strategy and how network development conducted by the Public Relations University of Riau.This study uses descriptive qualitative research, which seeks information and explain the phenomena that occur in accordance with the results obtained. Techniques used in collecting data through interviews, observation, and documentation. Informants in this study as many as four people. Examination of the validity of the data was performed using the extension of participation and triangulation techniques. Once the data is collected, then in the process through descriptive analysis of qualitative data, and then do an inference research.The results of this study explains that building a good relationship with the media is one of the strategies of media relations PR Riau University to be able to realize Good University Governwance. PR University of Riau establish specific strategies to manage a good relationship with the media, subscribe to the media, and the entire leadership of the head and its subsections public relations. Develop a strategy by using existing media in PR, build and maintain contact with the media, positioning the agency as a source of information, always coordinating with other subsections, and kemedian done to develop the network. It-al are interesting in this study is the disclosure required mass media colleagues, maintaining a good reputation and cooperation, take and give positive.Key words :media relations strategy, public relations University of riau, Good Governance